Peran Job Satisfaction Sebagai Variabel Intervening Dalam Hubungan Job Demand dan Job Resources Terhadap Work Engagement: The Role of Job Satisfaction as Intervening Variables in The Relationship of Job Demand and Job Resources to Work Engagement - Amaludin Prawira; Sri Lestari Prasilowati; Eka Avianti Ayuningtyas (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2022)
Bank DKI melakukan perubahan sistem kerja demi terjaganya produktivitas kerja selama Pandemi COVID-19 yang berpotensi mengurangi keterikatan kerja. Penelitian ini bertujuan melihat peran variabel job demand, job resources, job satisfaction, terhadap work engagement. Peneliti melakukan regresi terhadap variabel job demand, job resources, job satisfaction, dan work engagement. Mediasi dilakukan antara job demand dan job resources terhadap work engagement oleh job satisfaction. Purposive sampling dilakukan dengan jumlah 181 karyawan Bank DKI. Hasil penelitian menunjukkan bahwa seluruh variabel, baik job demand, job resources, dan job satisfaction signifikan memprediksi work engagement. Efek mediasi kepuasan terjadi baik pada variabel job demand maupun job resources. Bank DKI has changed the work system in order to maintain work productivity during the COVID-19 Pandemic so that it has the potential to reduce employee attachment. This study aims to see the role of variables of job demand, job resources, job satisfaction, and employee work engagement. Researchers regression of the variables of job demand, job resources, job satisfaction, and work engagement. Mediation is carried out between job demand and job resources for work engagement mediated by job satisfaction. Purposive sampling was carried out with a total of 181 employees of Bank DKI. The results showed that all variables, both job demand, job resources, and job satisfaction significantly predicted work engagement. The satisfaction mediation effect occurs both on the job demand and job resources variables.